Penguatan Kapasitas SDM dalam Implementasi Prinsip Environmental, Social, and Governance (ESG) pada Sektor Pertambangan: Suatu Kajian Literatur - Faisal Muchtasar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The mining sector faces global demands to integrate Environmental, Social, and Governance principles into all operational processes to support the industry’s sustainability. This study aims to analyze the strengthening of human resource capacity in the implementation of ESG in the mining sector through a systematic literature review using a conceptual-interpretive approach. The method employed involves a critical thematic synthesis of various reputable scientific sources to identify the relationship between human resource competencies, governance, and technological innovation. The results indicate that the success of ESG implementation is highly dependent on the quality of human resources possessing sustainability literacy, digital adaptability, and risk-based managerial competencies. The main weaknesses lie in fragmented governance, limited training, and low technology integration in HR management. Strengthening HR capacity through training, innovation, and green human resource management are key factors in accelerating the transformation toward a sustainable mining industry. This study provides a conceptual contribution toward building an integrative model between HR and ESG in the extractive sector.